Transformability in post-earthquake houses: towards a more sustainable design approach in Iran - Parva, Mohammad; Dola, Kamariah; Rahimian, Farzad Pour (Universiti Putra Malaysia, 2012)
Earthquake is one of the most calamitous disasters in Iran. The hazards of earthquake are always catastrophic not only during the disaster time but also for a long time after the disaster. Since Iran has particular financial and time constraints, hurriedly made post-earthquake emergence shelters often fail in complying with the minimum needs of the occupants. Thereby, such shelters have always been either abandoned or transformed substantially. Since the initial designs are not thoroughly tailored as to address the future’s transformational needs, such transformations need comprehensive replacements in terms of structure and construction. Regardless of the other issues that could be brought by these redundant works, they are always associated with an overwhelming waste of resources. In other words, the carbon-footprint of the buildings is often increased significantly only due to not so informed initial decisions by the designers. This study explored the difficulties of the post-disaster housing transformations in Lar city, Iran as a real-life case of study. This paper reports the needs and difficulties of people for transforming their post-earthquake houses. Due to the particular economic and socio-cultural conditions of Iran, the paper proposes to integrate “short-term” and “long-term” housing reconstruction models in order to help the victims have basic but transformable houses immediately after the disaster. In other words, the paper suggests that the potential transformation must be taken into account during very early design and construction stages. The paper contributes to design research and practice and opens new avenues towards more sustainable design with respect to post-earthquake housing projects.